KEMAMPUAN BERFIKIR KRITIS MAHASISWA PADA TUGAS BERWEBLOG MIKROBIOLOGI - Meiry Fadilah Noor (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
The science which discussed microbes is a part of the important concept in learning that implemented in curriculum 2013. To achieve national goals where students can critical, this research aims to analyze the critical thinking ability of students on courses of microbiology. Research methods a descriptive method which describe the phenomena of comment on the article through weblog about microbe daily life. There were 41st task had been commented on web. Then from the 41st, the 5th of article with commented were taken by purposive sampling technique to analyses critical response of the writer on comments. The results showed that, the writer able to argue with the reason, to observe and judge observation report, consider the credibility of a source, make deduction and the result of deduction, determine the term and judge the definition of the use of certain criteria (identify assumption).  But, the writers haven't been able to follow problem solving and metacognition, nor the sensitive in feeling and the same rhetoric in discussion and presentation. It was concluded that critical thinking skills students, still within the aspect on clarification to make decisions about belief or action. Keywords: critical thinking, weblog, daily life issue